Nuclear Magnetic Resonance Spectroscopy - Teresa Lehmann (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Nuclear Magnetic Resonance (NMR) spectroscopy is a nondestructive technique that can be used to characterize a wide variety of systems. Sustained development of both methodology and instrumentation have allowed NMR to evolve as a powerful technology, with applications in pure sciences, medicine, drug development, and important branches of industry. NMR provides precise structural information down to each atom and bond in a molecule, and is the only method for the determination of structures of molecules in a solution. This book compiles a series of articles describing the application of NMR in a variety of interesting scientific challenges. The articles illustrate the versatility and flexibility of NMR.